The impact of nirsevimab prophylaxis on RSV hospitalizations: a real-world cost-benefit analysis in Tuscany, Italy - Vieri Lastrucci; Martina Pacifici; Giorgia Alderotti; Monia Puglia; Elettra Berti; Federica Barbati; Lorenzo Lodi; Lorenzo Lodi; Silvia Boscia; Francesco Nieddu; Giuseppe Indolfi; Giuseppe Indolfi; et al. (Frontiers in Public Health, 2025)
BackgroundRespiratory Syncytial Virus (RSV) is the leading cause of hospitalizations in infants. The approval of nirsevimab, a long-acting monoclonal antibody, has extended the potential for RSV prophylaxis to all infants. This study assesses the cost–benefit of various Nirsevimab prophylaxis strategies for infants during their first RSV season in preventing RSV-associated hospitalization in the Tuscany region, Italy.MethodsThe analysis was conducted from the perspective of the healthcare payor. Real-world data from the Tuscany birth cohort (N = 21,017) experiencing their first RSV season in the 2023/2024 season were used to calculate the net benefit and benefit cost ratio (BCR) of three possible nirsevimab prophylaxis strategies compared with prophylaxis practices at the time of the study, which includes the use of palivizumab in eligible infants. RSV-associated hospitalizations and severe hospitalizations were considered as health outcomes. Sensitivity analyses were performed to identify influential variables.ResultsUnder prophylaxis practices at the time of the study, there were a total of 663 hospitalizations associated with RSV, including 102 severe cases, representing €5,247,645 in costs. An extended prophylaxis strategy with nirsevimab, including all infants born both before and during the RSV season, resulted in the highest number of hospitalizations avoided (378), with a BCR close to break-even (0.96). A seasonal-only strategy targeting infants born during the season prevented the fewest hospitalizations (252), showing a positive BCR of 1.15. Finally, a seasonal strategy with targeted catch-up, including also preterm infants born before the season, yielded the highest cost–benefit ratio (1.56), preventing 270 hospitalizations.ConclusionUniversal prophylaxis strategies with nirsevimab, targeting all infants during their first RSV epidemic season, substantially reduce hospitalization burdens without increasing economic pressure on the healthcare system. Although alternative strategies are more cost-effective, they prevent fewer hospitalizations, emphasizing the public health value of broader prophylaxis approaches.